Pendampingan Kelompok Tani Aneka Tanaman Memanfaatkan Sampah Organik dan Limbah Potong Ayam Sebagai Pupuk Organik Cair - Saronom Silaban; Murniaty Simorangkir; Choms Gary Ganda Tua Sibarani; Juniar Hutahaean; Kristin Wulan Liberti Vivanis Gulo; Litani Fivetrin Siregar; Fuaddinda Putri Salsabila; Martua Haojahan Saragih; Diana Fitri (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Liquid organic fertilizer (POC) is a solution of fermented organic matter derived from animal waste, plant residues, and humans. Using POCs in plants stimulates the better growth of stems, leaves, fruits, and seeds. This PKM activity aims to train partners of the "Aneka Tanaman" farmer group to use organic waste and chicken slaughter waste as liquid organic fertilizers. The main ingredients for making this POC are organic waste and cut waste obtained from the MMTC Medan market. The appropriate technology applied for the manufacture of this POC is a composter. The method of implementing the activities carried out is the P3 approach, namely planning, training, and mentoring. The activity results show that partners have the skills to process and utilize chicken slaughter waste and organic waste as liquid organic fertilizer. Using POC can reduce agricultural production costs; the selling price of farm products with POC is higher than using chemical fertilizers.